Crecimiento, mortandad y estado fitosanitario de la especie Ocotea aciphylla “canela moena” de la plantación N° 09 del CIEFOR - Puerto Almendra, Loreto – Perú. 2021 - García Pérez, José Marcial (2022)
The study was carried out in Forest Parcel No. 09 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Ocotea aciphylla “canela moena” plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by bands 8 and 9 with a value of 0,09 cm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 7 with a value of 6,68 cm. The Chi-square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0,00 <? = 0,05). The survival of cedar plants varies between 85% to 100% survival, while mortality reached 15%. The highest number of plants presented GOOD quality with 160 seedlings that represents 81,22% of the total, followed by REGULAR quality with 29 live individuals that indicates 14,72% and, finally, the least amount of individuals were observed in BAD quality with 8 seedlings that represented 4,06 % of the total. At a general level in the experiment Good quality was recorded for the Ocotea aciphylla seedlings at the end of the study. Similar studies are needed with other native forest species in Ciefor - Puerto Almendras.